Change of the chemical composition of potato plants when applying organic fertilizers under the conditions of the Chuvash Republic. Issue 1 (November 2020) - Vasilyev, O; Vasilyev, A; Eliseev, I; Schiptsova, N; Lozhkin, A; Fadeeva, N
Abstract: The experiments were carried out with the use of urban wastewater sludge from the city of Novocheboksarsk (Russia), crushed horns and hooves of cattle (horn-hoofed sawdust), semi-rotted cattle manure and wood ash on typical gray forest heavy loamy soil. By using sewage sludge as fertilizer for potatoes, the yield of tubers increased by almost 50%. However, the quality of potatoes in the first year of setting the experiment (2017) with the use of sewage sludge deteriorated: the ratio of K2 O/CaO in tubers decreased more than twice, the starch content decreased, and the amount of nitrates increased. The reason for the deterioration in the quality of tubers is the violation of the ratio of chemical elements (Ca, Mg and K) in the wastewater sludge, which led to the immobilization of potassium in the soil by microorganisms. The main indicators of the fertility of a typical gray forest soil at the end of the experiment improved significantly - the content of organic matter, mobile phosphorus and exchangeable potassium increased significantly. The possibility of one-time use of sewage sludge in increasing the fertility of depleted and degraded soils with the simultaneous use of potash mineral fertilizers to optimize the balance of potato nutrients in the soil is allowed.